2015
DOI: 10.1021/jp5126156
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Electrical and Optical Properties of Highly Conducting and Transparent Ta-Doped TiO2Polycrystalline Films

Abstract: We present a detailed study on polycrystalline transparent conducting Ta-doped TiO2 films, obtained by room temperature pulsed laser deposition followed by an annealing treatment at 550°C in vacuum. The effect of Ta as a dopant element and of different synthesis conditions are explored in order to assess the relationship between material structure and functional properties, i.e. electrical conductivity and optical transparency. We show that for the doped samples it is possible to achieve low resistivity (of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 63 publications
8
78
2
Order By: Relevance
“…[ 12 ] The thickness of all the analyzed fi lms is 150 ± 5 nm, as measured by scanning electron microscopy (SEM). The resistivity of all the as-deposited thin fi lms is about 10 Ω cm, with no particular dependence on the presence of doping; for as-deposited fi lms it was not possible to discern the contributions of charge carrier concentration and charge mobility because of the highly scattered values obtained in Hall measurements.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 12 ] The thickness of all the analyzed fi lms is 150 ± 5 nm, as measured by scanning electron microscopy (SEM). The resistivity of all the as-deposited thin fi lms is about 10 Ω cm, with no particular dependence on the presence of doping; for as-deposited fi lms it was not possible to discern the contributions of charge carrier concentration and charge mobility because of the highly scattered values obtained in Hall measurements.…”
Section: Resultsmentioning
confidence: 99%
“…[ 9 ] However, the discovery of donor doped TiO 2 as a promising new class of n-type TCO, [ 10 ] and the possibility of obtaining highly conducting and transparent polycrystalline Nb or Ta-doped TiO 2 (TaTO) thin fi lms on inexpensive glass substrates, open up new opportunities for a better suited energy level alignment at the device interfaces via an all TiO 2 -based confi guration (photoanode/selective layer and TCO). [11][12][13] Between the two mentioned donor doped compositions, Ta-doped TiO 2 is thought to have several advantages with respect to the more widely investigated Nb for transparent conductor applications, namely, higher mobility and dopant solubility. [ 14 ] Moreover, it has been suggested that donor-doped TiO 2 could be a superior material compared to undoped TiO 2 not only as a TCO but also as an electron selective layer (i.e., hole blocking layer) and photoanode.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations